(untitled) (Indian Journal of Child Health, 2014)
Background: The studies are required to better understand the needs of adolescents and to help policy makers to develop appropriate need-based adolescent reproductive health programs. Objectives: The objective was to assess the awareness among adolescents regarding various reproductive health issues and to assess their attitude and perceptions regarding reproductive health and human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Design: Community-based cross-sectional descriptive study. Participants: 423 adolescents of 11-19 years age group in two rural (219 students) and two urban (204 students) schools. Methodology: The survey used was a 4-part, 52-item self-administered questionnaire eliciting information on knowledge regarding reproductive health and HIV/AIDS. Result: Awareness of all reproductive health matters was suboptimum. Awareness was more in urban adolescents than in rural and in late teens than earlier teens. Overall, majority were aware of legal age of marriage (79%), two child family norm (90%), and birth spacing, disadvantages of early marriage, disfavor female feticide, and felt need for sex education (91%). Condoms were the most commonly known method of contraception among boys (80.15%) and oral pills among girls (60.24%). AIDS was the most well-known sexually transmitted disease (93.38%). Conclusion: Lacunae in awareness of all reproductive health matters suggests that young people’s sexual and reproductive health issues need to be further addressed and explored in order to promote safer and responsible sexual behavior.